Investigation of nicotianamine and 2′ deoxymugineic acid as enhancers of iron bioavailability in caco-2 cells - Beasley, Jesse T.; Hart, Jonathan J.; Tako, Elad; Glahn, Raymond P.; Johnson, Alexander A. T. (MDPI, 2019)
Nicotianamine (NA) is a low-molecular weight metal chelator in plants with high affinity for ferrous iron (Fe2+) and other divalent metal cations. In graminaceous plant species, NA serves as the biosynthetic precursor to 2′ deoxymugineic acid (DMA), a root-secreted mugineic acid family phytosiderophore that chelates ferric iron (Fe3+) in the rhizosphere for subsequent uptake by the plant. Previous studies have flagged NA and/or DMA as enhancers of Fe bioavailability in cereal grain although the extent of this promotion has not been quantified. In this study, we utilized the Caco-2 cell system to compare NA and DMA to two known enhancers of Fe bioavailability—epicatechin (Epi) and ascorbic acid (AsA)—and found that both NA and DMA are stronger enhancers of Fe bioavailability than Epi, and NA is a stronger enhancer of Fe bioavailability than AsA. Furthermore, NA reversed Fe uptake inhibition by Myricetin (Myr) more than Epi, highlighting NA as an important target for biofortification strategies aimed at improving Fe bioavailability in staple plant foods.